2018
DOI: 10.1101/348292
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Argininosuccinic aciduria fosters neuronal nitrosative stress reversed byAslgene transfer

Abstract: Argininosuccinate lyase (ASL) belongs to the liver-based urea cycle detoxifying ammonia, and the citrulline-nitric oxide cycle synthesising nitric oxide (NO). ASL-deficient patients present argininosuccinic aciduria characterised by hyperammonaemia and a multi-organ disease with neurocognitive impairment. Current therapeutic guidelines aim to control ammonaemia without considering the systemic NO imbalance. Here, we observed a neuronal disease with oxidative/nitrosative stress in ASL-deficient mouse brains. A … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 71 publications
(83 reference statements)
1
28
0
Order By: Relevance
“…To this end, Asl Neo/Neo mice received protein-restricted diet and daily administration of Na-benzoate and L-Arg in combination with either TB-1 or vehicle, started on day ten of life and lasting for 3 weeks. Consistent with previous data (Ashley et al, 2018;Baruteau et al, 2018;Burrage et al, 2020;Erez et al, 2011), vehicle-treated Asl Neo/Neo mice showed vacuolated hepatocyte cytoplasm by hematoxylin and eosin (H&E) staining in contrast to WT mice, whereas TB-1 treatment markedly improved the microscopic changes of liver architecture (Fig. 3A).…”
Section: Tat-beclin-1 Reduced Injury and Abnormal Glycogen Depositionsupporting
confidence: 91%
See 1 more Smart Citation
“…To this end, Asl Neo/Neo mice received protein-restricted diet and daily administration of Na-benzoate and L-Arg in combination with either TB-1 or vehicle, started on day ten of life and lasting for 3 weeks. Consistent with previous data (Ashley et al, 2018;Baruteau et al, 2018;Burrage et al, 2020;Erez et al, 2011), vehicle-treated Asl Neo/Neo mice showed vacuolated hepatocyte cytoplasm by hematoxylin and eosin (H&E) staining in contrast to WT mice, whereas TB-1 treatment markedly improved the microscopic changes of liver architecture (Fig. 3A).…”
Section: Tat-beclin-1 Reduced Injury and Abnormal Glycogen Depositionsupporting
confidence: 91%
“…To investigate the efficacy of autophagy enhancement for therapy of argininosuccinic aciduria (ASA), the second most frequent UCD (Baruteau et al, 2019a), we investigated TB-1 treatment in the hypomorphic murine model of ASL deficiency (Asl Neo/Neo ) that expresses approximately 16% of residual enzyme activity and recapitulates the main biochemical and clinical abnormalities of ASA patients (Baruteau et al, 2018;Burrage et al, 2020;Kho et al, 2018;Nagamani et al, 2012). Besides impaired urea synthesis and ammonia detoxification, systemic manifestations of ASA, such as reduced body weight, increased blood pressure, and reduced survival are also associated with nitric oxide (NO)-deficiency (Baruteau et al, 2018;Erez et al, 2011;Kho et al, 2018;Nagamani et al, 2012). Asl Neo/Neo mice treated only with TB-1 showed increased survival compared to vehicle-treated controls that started dying by ten days of age ( Fig.…”
Section: Tat-beclin-1 Enhances Ureagenesis and Corrects Metabolic Abnmentioning
confidence: 99%
“…Recently, several alternative mechanisms in the pathophysiology of ASA have been postulated such as cumulative exposure to disease‐specific neurotoxic biomarkers, high cerebral concentrations of argininosuccinic and guanidinosuccinic acid and cerebral deficiency of nitric oxide due to NOS deficiency (Baruteau et al, 2017; Erez, Nagamani, & Lee, 2011; Erez, Nagamani, Shchelochkov et al, 2011; Posset, Gropman et al, 2019). Moreover, the neuronal ammonia‐independent cerebral disease was shown to be caused by oxidative/nitrosative stress through an imbalance of NO metabolism in an ASL‐deficient mouse model, a mechanism which is not targeted by current therapeutic principles (Ashley, Nordin, Buza, Greig, & Wilson, 2018; Baruteau et al, 2018). The importance of brain‐specific pathomechanisms in ASA is also highlighted by the fact, that the cognitive outcome at the last regular visit of these patients is not relevantly affected by the initial NH 4 + max unlike in other UCDs (Posset, Gropman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is substantiated by recent findings that the severity of the initial HAE is an important but not the only factor associated with a favorable or poor cognitive outcome (Baruteau et al, 2019; Posset, Gropman et al, 2019; Waisbren, Gropman, Members of the Urea Cycle Disorders Consortium, & Batshaw, 2016). The paradox reflecting that individuals with ASA perform worse in cognitive testing as compared to other UCDs despite lower frequencies of HAEs, suggests that other ammonia‐independent pathomechanisms might underlie the disease, such as disturbed NO metabolism causing cerebral oxidative/nitrosative stress (Baruteau et al, 2018). Moreover, interallelic complementation between specific variants has been shown to contribute to phenotypic variability in ASA (McInnes, Shih, & Chilton, 1984; Walker et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In Asl Neo/Neo mice, decreased levels of reduced glutathione were observed in liver and partially improved after liver‐directed gene therapy . Markers of oxidative stress were elevated in murine plasma, urine, and in tissues .…”
Section: Therapeutic Perspectives and Monitoringmentioning
confidence: 99%